Coming back together: a qualitative survey study of coping and support strategies used by people to cope with extended difficulties after the use of psychedelic drugs - Robinson, Oliver C.; Evans, Jules; Luke, David; McAlpine, Rosalind; Sahely, Aneta; Fisher, Amy; Sundeman, Stian; Ketzitzidou Argyri, Eirini; Murphy-Beiner, Ashleigh; Michelle, Katrina; Prideaux, Ed (Frontiers in Psychology, 2024)
Introduction A growing body of literature is investigating the difficulties that some individuals encounter after psychedelic experiences. Existing research has explored the nature and predictors of these difficulties; however, a research gap exists in understanding how individuals endeavour to cope with such difficulties. Methods The current study collected data from an international cohort of 608 participants who reported experiencing difficulties that persisted for at least one day after a psychedelic experience. They provided written data on how they used coping strategies to alleviate these difficulties. The qualitative analysis of the written data on coping was conducted using Structured Tabular Thematic Analysis. Results A wide range of individual and social coping strategies were employed that were found helpful. The most common individual strategies were meditation and prayer, followed by self-educational activities such as reading and journaling. The most prevalent forms of social coping involved seeking support from friends or family members, followed by obtaining assistance from a therapist or coach. Features of social coping that were reported to be helpful included feeling heard/accepted, a non-judgemental attitude and sharing similar experiences. Discussion Our findings hold potential for informing the design of therapeutic interventions and educational resources aimed at enhancing positive outcomes for those experiencing extended difficulties after psychedelic use.